2015
DOI: 10.1016/j.jacc.2014.10.040
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Aging on Human Mesenchymal Stem Cell Therapy in Ischemic Cardiomyopathy Patients

Abstract: BACKGROUND The role of patient age on the efficacy of mesenchymal stem cell (MSC) therapy in ischemic cardiomyopathy (ICM) is controversial. OBJECTIVE We sought to determine whether the therapeutic effect of culture-expanded MSCs persists even in older subjects. METHODS Patients with ICM who received MSCs via transendocardial stem cell injection (TESI) as part of the TAC-HFT (n = 19) and POSEIDON (N = 30) clinical trials were divided into 2 age groups: <60 versus ≥60 years. Functional capacity was measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(56 citation statements)
references
References 41 publications
0
53
1
2
Order By: Relevance
“…Understanding the effect of aging on MSCs is crucial for autologous therapy for older patients, who are typically afflicted by cardiovascular diseases. In a recently published sub-study 156 from the TAC-HFT and POSEIDON trials, it was reported that older individuals did not have an impaired response to MSC therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the effect of aging on MSCs is crucial for autologous therapy for older patients, who are typically afflicted by cardiovascular diseases. In a recently published sub-study 156 from the TAC-HFT and POSEIDON trials, it was reported that older individuals did not have an impaired response to MSC therapy.…”
Section: Introductionmentioning
confidence: 99%
“…All other authors, who are not complex processes in vivo like multilineage growth and differentiation, angiogenesis, and ventricular remodeling, while pharmacologic therapy predictably targets a single cellular receptor for efficacy. Further confounding CCT is the choice of therapeutic cells (4,9) and cell delivery techniques (10), as well as the impact of host factors (11), suggesting that new approaches are needed to link data between model systems (12).…”
Section: Industry Supportmentioning
confidence: 99%
“…Findings from TAC-HFT and POSEIDON clinical trials using MSCs in patients with ischemic cardiomyopathy demonstrate that the chronological age of the recipient does not affect the efficacy of the treatment [37]. Functional improvements and scar size reduction following cell therapy were comparable between patients older and younger than 60 years of age.…”
Section: Alternative Perspectives On Stem Cells and Cardiac Agingmentioning
confidence: 99%
“…Functional improvements and scar size reduction following cell therapy were comparable between patients older and younger than 60 years of age. Although the cellular and functional characteristics of the donor MSCs as well as the recipient’s endogenous CPCs were not studied, this finding demonstrates that stem cell therapy using exogenously expanded MSCs can circumvent chronological age of the recipient and potentiate cardiac repair [37]. Treatment with MSCs also enhances proliferation and differentiation of endogenous CPCs, suggesting that stem cell interactions may be an important mechanism for success in stem-cell based therapy [38].…”
Section: Alternative Perspectives On Stem Cells and Cardiac Agingmentioning
confidence: 99%